Determinants of sleep and morning alertness in elite short-track speed skaters during the preseason - Varesco, G.; Renaud-Roy, A.; Germain, M.; Szocs, S.; Pattyn, N.; Bieuzen, F.; Simonelli, G. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Sleep in elite athletes could be compromised by stressors such as high training volumes and mediated by factors related to individual characteristics and training schedule. However, longitudinal real-world data capturing the factors influencing sleep in elite athletes remain scarce. We aimed to determine what predicts sleep quantity, sleep quality, and morning cognitive readiness in elite speed skaters of the Canadian short-track World Cup team.